Implementasi Electronic Health Record (EHR) Pada Poli Rawat Jalan Di Rumah Sakit Umum Daerah Ratu Zalecha Martapura - Nina Rahmadiliyani Rahmadiliyani; Putri Putri; Rina Gunarti (Jurnal Kesehatan Indonesia, 2019)
A system of Electronic Health Record (EHR) is an activity computerized the contents of the medical record and process related. Based on the preliminary studies in Hospital of Ratu Zalecha Martapura obtained that already some clinics that implement EHR systems and for some clinics will get their turn to apply the system. The purpose of this research was to identify the security system (security), clinical support (clinical support), and reports (report) on the system of the EHR. The method of this research uses descriptive research with qualitative analysis. Research instrument this is manual observation and interview guidelines. This research was conducted to 8 informant head installation medical record, IT officers, three doctors and three nurses. The results of research at in Hospital of Ratu Zalecha Martapura to be able to access the EHR user must use a username and password. Username and password are made according to their respective limits and authority. Clinical support in the system is good, doctors and nurses fill their own diagnoses into EHR applications, service time is more effective and more efficient so as to improve patient services. Reports produced were reports of 10 major outpatient diseases, outpatient visit reports, daily outpatient census reports, RL1, RL2, RL3, RL4 and RL5.